Sequential eIF5 binding to the charged disordered segments of eIF4G and eIF2β stabilizes the 48S pre-initiation complex and promotes its shift to the initiation mode - Singh, Chingakham Ranjit; Watanabe, Ryosuke; Chowdhury, Wasimul Q.; Hiraishi, Hiroyuki; Murai, Marcelo J.; Yamamoto, Yasufumi; Miles, David; Ikeda, Yuka; Asano, Masayo; Asano, Katsura (My University, 2012)
During translation initiation in Saccharomyces cerevisiae, an Arg- and Ser-rich segment (RS1 domain) of eIF4G and the Lys-rich segment (K-boxes) of eIF2β bind three common partners, eIF5, eIF1 and mRNA. Here we report that both of these segments are involved in mRNA recruitment and AUG recognition by distinct mechanisms. First, the eIF4G-RS1 interaction with eIF5-C-terminal domain (CTD) directly links eIF4G to the preinitiation complex (PIC) and enhances mRNA binding. Second, eIF2β-K-boxes increase mRNA binding to the 40S subunit in vitro, in a manner reversed by eIF5-CTD. Third, mutations altering eIF4G-RS1, eIF2β-K-boxes and eIF5-CTD restore the accuracy of start codon selection impaired by a eIF2β mutation in vivo, suggesting that the mutual interactions of the eIF segments within the PIC prime the ribosome for initiation in response to start codon selection. We propose that the rearrangement of interactions involving eIF5-CTD promotes mRNA recruitment through mRNA binding by eIF4G and eIF2β and assists the start-codon-induced release of eIF1, the major antagonist of establishing tRNA[subscript i][superscript Met]:mRNA binding to the P-site.
Sequential eukaryotic translation initiation factor 5 (eIF5) binding to the charged disordered segments of eIF4G and eIF2β stabilizes the 48S preinitiation complex and promotes its shift to the initiation mode
Keywords: Eukaryotic translation; Initiation factors; eIF5; eIF4G; eIF2β